This is the Pythagorean theorem where the 2 legs of a triangle squared add up to equal the squared hypotenuse (a^2 + b^2 = c^2)
The equation would be
12^2 + 5^2 = x^2
144 + 25 = 169
The square root of 169 = 13
Answer - 13 ft
The algebraic expression for the statement Cindy's age, x, is 3 times her age 6 years ago is 3(x-6).
The given statement is Cindy's age, x, is 3 times her age 6 years ago.
We need to represent the given statement as the algebraic expression.
<h3>What is an algebraic expression?</h3>
In mathematics, an algebraic expression is an expression built up from integer constants, variables, and algebraic operations.
6 years ago Cindy's age(x) is x-6.
3 times Cindy's age=3(x-6)
Therefore, the algebraic expression for the statement Cindy's age, x, is 3 times her age 6 years ago is 3(x-6).
To learn more about the algebraic expression visit:
brainly.com/question/953809.
#SPJ1
Answer:
y= 2x-3 m=2 b= -3
Step-by-step explanation:
we distribute 2(x-2)
y-1 = 2(x-2)
y-1 = 2x-4
then add one to both sides
y-1= 2x -4
+1 +1
since it is negative four and you are adding one it would be -3
y= 2x -3 that is your slope intercept form.
y= mx +b so m=2 and b= -3
Answer:
x=3
Step-by-step explanation:
3(2x+3)=27
2x+3=27/3=9
2x=9-3=6
x=6/2=3
You have to give the problem and not just the options for me to solve